Behind the Suspense: “Knowledge” as “Prey” in the Film Possession (London Journal of Research In Humanities and Social Sciences, 2025)
The film Possession employs detective narrative techniques to build a suspenseful, symbol-rich structure, intertwining the plot with the pursuit of “knowledge” and transforming the viewing experience into a metaphor for the quest for understanding. This paper analyzes the construction of suspense and the deeper implications of “knowledge” as “prey” in Possession from three perspectives. First, it analyzes the film’s detective techniques and their role in uncovering truth. Second, it explores how unsent letters ignite the audience’s interpretive desire. Lastly, it examines unresolved mysteries, emphasizing philosophical reflections on “knowledge” and theory. These three dimensions are interrelated, collectively emphasizing the pivotal role of “knowledge” exploration in promoting female empowerment and fostering deeper theoretical reflections.
Keywords: detective techniques; knowledge; reading desire; suspense; theoretical reflection